Improving the tax dispute resolution process in Nigeria with special attention to the tax appeal tribunal: insights from South Africa with an emphasis on tax courts - Esomeju, Nneka Cecilia (Department of Commercial Law, 2022)
The patent problems experienced in Nigeria's tax dispute resolution processes inspired this thesis. The disbanding of specialist tax tribunals by the Nigerian higher courts epitomised the disorder. The South African tax dispute resolution regime was reviewed primarily to identify practices that could be recommended to improve the Nigerian regime. The research questions in respect of improving the tax dispute resolution system in Nigeria are the following: How has the current tax dispute resolution system in Nigeria evolved? How should it evolve further? Can South Africa provide insights about the direction it should take? To answer the research questions, the tax dispute resolution environments in Nigeria and South Africa were assessed based on the convergent norms of good dispute resolution common to both. In this assessment of the two jurisdictions, emphasis was placed on judicial independence, access to justice, procedural fairness, administrative or judicial discretion, and timeousness. A combination of empirical and doctrinal methods was used. The key findings were as follows: (a) some current shortcomings can be explained by the historical evolution of the Nigerian tax environment, chiefly because taxation was introduced at different periods in the different regions of Nigeria and laws were not amended in a uniform manner; (b) there is no uniform centralised in-house dispute resolution process in the Nigerian federal tax authority; (c) the federal tax authority prefers to settle disputes out of court; (d) taxpayers comply better when a diplomatic approach to settling disputes is used by the tax authority; (e) Lagos was the most tax-compliant and litigious state in Nigeria; (f) conflicting decisions by courts of commensurate rank did not change the pre-existing practices of the tax authority as the authority will continue with the practice until it is vacated by a higher court; and (g) litigation was possibly a form of tax planning for some taxpayers. Recommendations were formulated based on the notion that convergent norms of good dispute resolution require the improvement of existing frameworks and practices. The reform of legislation and operational aspects of the Nigerian regime was also recommended. Key recommendations include (i) the retention of the TAT as a venue for the resolution of tax disputes; and (ii) the introduction of an in-house mediation process.